IMPLEMENTASI AHP-TOPSIS DAN NAÏVE BAYES DALAM SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN BIMBINGAN KONSELING SISWA - Anak Agung Sandatya Widhiyanti; I Made Candiasa; Kadek Yota Ernanda Aryanto (LPPM STMIK STIKOM Indonesia, 2021)
Student development cannot be separated from the influence of the surrounding environment, be it physical, psychological, and social. The inherent nature of the environment is change, if change is difficult to predict, it will create behavioral gaps from students. For example, problems that are often experienced by students are difficulties in increasing grades so that the scores are relatively low, the level of class attendance is minimal, the learning environment in the classroom whether it supports students to be able to participate in learning activities or not, violations of school rules, and so on. The purpose of this study is to help provide decision recommendations for students who will be given priority in counseling guidance and counseling services. The method used for calculations on the SPK is a combination of AHP-TOPSIS and Naïve Bayes Classifier. AHP is used to find the weight value of each criterion, TOPSIS is used in the ranking process while Naïve Bayes is used to determine counseling services. The results of this study are in the form of a decision support system, which can facilitate the decision-making process, and can provide recommendations for students who are prioritized for counseling and counseling services